Environmental and Product Contamination during the Preparation of Antineoplastic Drugs with Robotic Systems - Krämer Irene; Federici Matteo; Schierl Rudolf (De Gruyter, 2018)
Robotic systems are designed to minimize the exposure to antineoplastic drugs during automated preparation. However, contamination cannot be completely excluded. The aim of the study was to evaluate the contamination with antineoplastic drugs on the working surfaces and on the outer surface of the ready-to-use products (infusion bags and syringes) during automated preparation with different versions of a robot and manual preparation.